An Association of Adverse Childhood Experiences with Binge Drinking in Adulthood: Findings from a Population-Based Study. (7th February 2022) - Baiden, Philip; Onyeaka, Henry K.; Kyeremeh, Emmanuel; Panisch, Lisa S.; LaBrenz, Catherine A.; Kim, Yeonwoo; Kunz-Lomelin, Alan
Abstract: Background : Adverse childhood experiences (ACEs) are a major public health issue linked to negative health outcomes. Yet, few recent studies drawing on national data have examined the association between ACEs and binge drinking. Objective : The objective of this study was to examine the association between ACEs and binge drinking among adults in the United States and whether this association is dependent on sex. Methods : Data for this study were obtained from the 2019 Behavioral Risk Factor Surveillance System survey. An analytic sample of 41, 322 adults aged 18–64 years (50.7% male) from 17 states was analyzed using binary logistic regression. The outcome variable was binge drinking, and the main explanatory variable was ACEs. Results : Of the 41, 322 respondents, 21.3% engaged in binge drinking. About 30% of the respondents had no ACEs and 23.9% had four or more ACEs. In the multivariable logistic regression, we observed that sex moderated the association between ACEs and binge drinking. Odds were 1.36 times higher for females who experienced two ACEs (aOR = 1.36 p < .05, 95% CI = 1.04–1.77) and 1.58 times higher for females who experienced three ACEs (aOR = 1.58 p < .01, 95% CI = 1.17–2.12) to engage in binge drinking. Other factors associated with binge drinking include younger age, non-Hispanic White, higher income level, higher education, not being married, being overweight, and history of cigarette smoking. Conclusion : The findings of this study underscore the importance of developing sex-appropriate screening and intervention strategies to support individuals exposed to ACEs and potentially mitigate negative health outcomes later in life.